The Role of Teachers in Shaping Islamic Education Values in Elementary Schools Theory: Social Construction Peter L Berger - Nuha, Farahah Kamilatun (International Journal of Basic Educational Research, 2025)
This research aims to analyze the role of teachers in forming values ​​in Islamic education in elementary schools using Peter L. Berger's social construction theory. This research uses the literature study method. Social construction theory makes Islamic education not only carry an academic dimension but also a means of forming character, morals, norms, and educational values ​​for students. Teachers are the main agents in the educational environment, having a very important role in shaping values ​​in the social construction of Islamic education. The role of teachers as educators is very influential in optimizing the competencies possessed by students so that they are ready and able to interact and adapt in real life. The teacher's role is not only limited to delivering material in class based on learning objectives but has a much greater moral responsibility, namely carrying out the process of internalizing values ​​and norms to students, to shape students' character based on applicable values ​​and norms